2018
DOI: 10.1108/ara-06-2017-0102
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility (CSR) practices by SIN firms

Abstract: Purpose The purpose of this paper is to examine corporate social responsibility (CSR) practices of SIN firms. SIN firms are firms from controversial sectors such as tobacco, alcohol, gambling and firearms. Design/methodology/approach This paper explains contrasts CSR practices of SIN firms with similar size and industry non-SIN counterparts. Findings This paper shows that SIN firms conduct more CSR practices than non-SIN firms. This paper also finds that CSR practices of SIN firms are value relevant only w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
2
13
1
Order By: Relevance
“…Increased support and trust from investors, will make the firm performance will increase then the firm will achieve the targeted profit (Lindawati & Puspita, 2015). CSR carried out by the company has a positive significant relationship to company performance, this is in line with the results of research from Melinda & Wardhani (2020), Bajic & Yurtoglu (2018), Alareeni & Hamdan (2020), Radhouane et al (2018), Nirino et al (2020), Fiandrino et al (2019), Aboud & Diab (2018), Sharma & Song (2018), Park (2017), Nirino et al (2020), Fiandrino et al (2019), Aboud & Diab (2018), Sharma & Song (2018), Park (2017), Griselda et al (2020), Alipour et al (2019), Buallay (2019), Nekhili et al (2017), dan Devie et al, (2020). H1: CSR affects performance of mining companies in Indonesia…”
Section: Relationship Of Csr To Performancesupporting
confidence: 72%
See 1 more Smart Citation
“…Increased support and trust from investors, will make the firm performance will increase then the firm will achieve the targeted profit (Lindawati & Puspita, 2015). CSR carried out by the company has a positive significant relationship to company performance, this is in line with the results of research from Melinda & Wardhani (2020), Bajic & Yurtoglu (2018), Alareeni & Hamdan (2020), Radhouane et al (2018), Nirino et al (2020), Fiandrino et al (2019), Aboud & Diab (2018), Sharma & Song (2018), Park (2017), Nirino et al (2020), Fiandrino et al (2019), Aboud & Diab (2018), Sharma & Song (2018), Park (2017), Griselda et al (2020), Alipour et al (2019), Buallay (2019), Nekhili et al (2017), dan Devie et al, (2020). H1: CSR affects performance of mining companies in Indonesia…”
Section: Relationship Of Csr To Performancesupporting
confidence: 72%
“…However, previous studies found differences in empirical results. Melinda & Wardhani (2020) ; Bajic & Yurtoglu (2018) ; Alareeni & Hamdan (2020) ; Radhouane et al (2018) ; Nirino et al (2020) ; Fiandrino et al (2019) ; Aboud & Diab (2018) ; Sharma & Song (2018) ; Park (2017) ; Nirino et al (2020) ; Fiandrino et al (2019) ; Aboud & Diab (2018) ; Sharma & Song (2018) ; Park (2017) ; Griselda et al (2020) ; Alipour et al (2019) ; Buallay (2019) ; Nekhili et al (2017) ; Devie et al, (2020) found that the effect of CSR on company performance was significantly positive. Meanwhile, the research researched by Feng & Glenn Kreuze (2017) ; Buallay, Fadel, et al (2020) ; Buallay, Kukreja, et al (2020) found the effect of CSR on company performance was significantly negative.…”
Section: Introductionmentioning
confidence: 99%
“…Their research also provides tools to validate the relevance of ESG disclosure. Finally, and closely related to the focus of our study, the study by [17] provides evidence that sin stocks disclose more ESG information and invest more in environmentally and socially responsible practices than firms operating in non-controversial sectors. More important, ref.…”
Section: Incentives To Reporting Esg Informationsupporting
confidence: 57%
“…Despite this, other research shows that, at the same time, SIN firms may be less responsible than peers. So, the ESG performance of this particular industry group is lower than that of companies associated with technology, resources, and other markets [26][27][28].…”
Section: Esg Effects On Cfpmentioning
confidence: 99%